A study on the reproductive characteristics and invasiveness of Crassocephalum rubens and Crassocephalum crepidioides - Cui, Xianliang; Luo, Yating; Luo, Yinling (Frontiers in Ecology and Evolution, 2025)
IntroductionThis study aims to explore the reproductive characteristics and invasiveness of Crassocephalum rubens and Crassocephalum crepidioides, offering valuable insights for the future management and control of invasive plant species.MethodsA series of experiments were conducted on the invasive plants C. rubens and C. crepidioides, including pollen viability determination, flowering dynamics observation, stigma receptivity tests, pollen-ovule ratio analysis, artificial bagging experiments, and seed germination tests.ResultsThe results indicated that: (1) C. rubens had significantly more florets per inflorescence (246.1 ± 70) compared to C. crepidioides (154.6 ± 16.3), and a longer floral longevity (11.3 ± 0.9 days vs. 8.5 ± 1.6 days); (2) The P/O ratio of C. rubens was 1020.8 ± 398.57, indicating a facultative outcrossing system, while that of C. crepidioides was 240 ± 69.28, suggesting a facultative selfing system; (3) The pollen viability of C. rubens remained above 80% (84.45%-59.85%) between days 3 and 5 of flowering, whereas C. crepidioides reached 80.59% only on day 5, with a shorter duration; (4) Both species exhibited high seed set rates under natural conditions (C. rubens: 92.97%, C. crepidioides: 95.53%), with reproductive modes including autogamy and self-compatibility; (5) Germination rates were 93.9% for C. rubens and 97.9% for C. crepidioides, with C. crepidioides germinating earlier and surpassing 50% germination sooner.DiscussionBoth C. rubens and C. crepidioides possess traits such as self-compatibility, high seed set rates, high germination rates, and year-round growth, which enable them to rapidly establish and spread in new environments. While there is no significant difference in seed set or germination rates between the two species, C. rubens shows advantages in floral longevity and seed production. These factors may provide C. rubens with a stronger competitive edge in natural environments, potentially facilitating its dominance over C. crepidioides in certain conditions.